2003
DOI: 10.1124/mol.64.5.1117
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Signaling in Human Heart: Shift from the Cyclic AMP to the Arachidonic Acid Pathway

Abstract: We have recently established that enhancement of intracellular calcium cycling and contraction in response to ␤ 2 -adrenergic receptor (␤ 2 -AR) stimulation exclusively relies on the activation of the cytosolic phospholipase A 2 (cPLA 2 ) and arachidonic acid production, via a pertussis toxin-sensitive G protein (possibly Gi), in embryonic chick cardiomyocytes. We aimed to investigate the relevance of the ␤ 2 -AR/Gi/cPLA 2 pathway in the human myocardium. In left ventricular biopsies obtained from explanted he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Thus, in heart muscle cells, ␤ 2 -adrenegic receptor signaling can switch from G s to G i (Daaka et al, 1997;Hasseldine et al, 2003;Hill and Baker, 2003;Magocsi et al, 2007), and signaling from G i to mediators known to be upstream of PKC (Herrlich et al, 1996;Daaka et al, 1997;Steinberg, 1999;Mackay and Mochly-Rosen, 2001;Pavoine et al, 2003;Pavoine and Defer, 2005) or to PKC (Fraser et al, 2000;Otani et al, 2003;Paruchuri and Sjolander, 2003) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in heart muscle cells, ␤ 2 -adrenegic receptor signaling can switch from G s to G i (Daaka et al, 1997;Hasseldine et al, 2003;Hill and Baker, 2003;Magocsi et al, 2007), and signaling from G i to mediators known to be upstream of PKC (Herrlich et al, 1996;Daaka et al, 1997;Steinberg, 1999;Mackay and Mochly-Rosen, 2001;Pavoine et al, 2003;Pavoine and Defer, 2005) or to PKC (Fraser et al, 2000;Otani et al, 2003;Paruchuri and Sjolander, 2003) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors, like D 2 -like receptors, can be coupled to PLA 2 activation and AA release (Berg et al, 1998;Garcia and Kim, 1997;KurraschOrbaugh et al, 2003;Pavoine et al, 2003;Qu et al, 2003). However, raclopride's ability to block k* increments following 2.5 mg/kg D-amphetamine (Table 2) indicates that the increments did not directly involve serotonin or epinephrine-initiated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic, serotonergic and noradrenergic receptors can be coupled by G-proteins to different effector enzymes, including phospholipase A 2 (PLA 2 ). Phospholipase A 2 activation releases arachidonic acid (AA,) from membrane phospholipids (Axelrod, 1990;Garcia and Kim, 1997;Nilsson et al, 1998;Pavoine et al, 2003;Vial and Piomelli, 1995). Arachidonic acid and its eicosanoid products are important second messengers that can influence membrane excitability, regional cerebral blood flow (rCBF), gene transcription, mood, and sleep (Chen and Bazan, 2005;Fitzpatrick and Soberman, 2001;Niwa et al, 2000;Rapoport and Bosetti, 2002;Shimizu and Wolfe, 1990;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Semi-quantitative RT-PCR was carried out on a Light Cycler (Roche Diagnostic), as previously described [35]. Oligonucleotide primers (MWG Biotech) were as follows: Rat 18S, 5'-GTAACCCGTTGAACCCCATT-3' (sense) and 5'-CCATCCAATCGGTAGTAGCG-3' (antisense); rat ANP, 5'-AGCGAGCAGACCGATGAAGC-3' (sense) and 5'-GCAGAGTGGGAGAGGTAAGGC-3' (antisense); rat ßMHC, 5'-ATTCTCCTGCTGTTTCTTTACTTG-3' (sense) and 5'-TGACTTTGCCACCCTCTCG-3' (antisense).…”
Section: Rna Preparation and Rt-pcrmentioning
confidence: 99%